1993
DOI: 10.1136/bjo.77.3.158
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of the blood-ocular barrier in adolescent and adult diabetic patients.

Abstract: The permeability of the blood-ocular barrier was examined by fluorophotometry in adolescent and adult diabetic patients before the onset ofretinopathy. (r=0.79, p<0-0001) with the duration ofdiabetes. Anterior chamber (AQ) values, an index ofthe permeability ofthe blood-aqueous barrier (BAB), increased in the adolescent diabetic patients compared with the controls and showed a significant positive correlation with glycosylated haemoglobin levels. No significant differences from the controls were observed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…Abnormal retinal vascular permeability caused by BRB breakdown precedes the appearance of clinical diabetic retinopathy [2,3]. Our study shows that retinal vascular permeability, as measured by VFP, increased significantly in the STZ-induced diabetic rats compared with control rats.…”
Section: Discussionmentioning
confidence: 48%
“…Abnormal retinal vascular permeability caused by BRB breakdown precedes the appearance of clinical diabetic retinopathy [2,3]. Our study shows that retinal vascular permeability, as measured by VFP, increased significantly in the STZ-induced diabetic rats compared with control rats.…”
Section: Discussionmentioning
confidence: 48%
“…Increased values of AGEs in the vitreous in patients with PDR seem to be related to breakdown of the BRB. Furthermore, some authors reported that permeability of the bloodaqueous barrier (BAB) increased in patients with PDR (22,23). We speculated that increased corneal AGEs in patients with PDR may be caused by an increase of AGEs in the aqueous humor and vitreous resulting from breakdown of the BRB and/or BAB.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple causes of blood retinal barrier breakdown have been identified, including infection (Cellini and Baldi, 1991;Pepose, et al, 1985), diabetes (Lobo, et al, 2000;Schalnus and Orloff, 1995;Yoshida, et al, 1993), and intraocular surgery (Men, et al, 2003). Associations have been reported between the breakdown of the blood retinal barrier and almost every retinal disease, particularly vascular retinopathies and pigment epitheliopathies (Forrester and Menamin, 1999).…”
Section: Blood Retinal Barrier Permeabilitymentioning
confidence: 99%